The Safe Drinking Water and Clean Water Acts: A Large City View - Branch, Chris (Maine Policy Review, 1992)
The Safe Drinking Water Act of 1986 and the Clean Water Act Amendments of 1991 present significant financial and technical challenges to municipalities in Maine and other states as they struggle to meet compliance standards. Chris Branch, public works director and city engineer for Lewiston, presents a large community perspective.